Disaster Risk Management through the Use of ICT: a Review - Rodríguez Godínez, Gregoria Rosa (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2021)
The importance of knowledge management is the difference between prevention and risk. The objective of this article is to review the administrative areas applicable to disaster risk management; to know case studies from India and Japan of how they use Information and Communication Technologies (ICTs), and through the management of these technologies, they generate synergies to face risks to which the population is exposed. Understanding disaster risk as the interrelation between threats and conditions of vulnerability of people, the purpose is to disseminate knowledge management in auxiliary organizations that provide help.